Multiply eqn 1 by 2 and reverse. Multiply the delta H value by 2 and change the sign.
Multiply eqn 2 by 2 and reverse it. Multiply the delta H value by 2 and change the sign.
Add the new eqn 1 + eqn 2 along with eqn 3 and you get twice the equn you want. Add new delta H values for total and take half of it.
Calculate delta H for the reaction below using Hess's Law:
C2H6 ---> C2H2 + 2H2
------------------------------------------
C2H2 + 5/2O2 --> 2CO2 + H2O (H = -1300 kJ)
2H2 + O2 --> 2H2O (H= -572 kJ)
2C2H6 + 7O2 --> 4CO2 + 6H2O (H= -3120 kJ)
2 answers
842.5